A comprehensive spectrometry study of a stray neutron radiation field in scanning proton therapy. (11th May 2016) - Mares, Vladimir; Romero-Expósito, Maite; Farah, Jad; Trinkl, Sebastian; Domingo, Carles; Dommert, Martin; Stolarczyk, Liliana; Van Ryckeghem, Laurent; Wielunski, Marek; Olko, Pawel; Harrison, Roger M
Abstract: The purpose of this study is to characterize the stray neutron radiation field in scanning proton therapy considering a pediatric anthropomorphic phantom and a clinically-relevant beam condition. Using two extended-range Bonner sphere spectrometry systems (ERBSS), Working Group 9 of the European Radiation Dosimetry Group measured neutron spectra at ten different positions around a pediatric anthropomorphic phantom irradiated for a brain tumor with a scanning proton beam. This study compares the different systems and unfolding codes as well as neutron spectra measured in similar conditions around a water tank phantom. The ten spectra measured with two ERBSS systems show a generally similar thermal component regardless of the position around the phantom while high energy neutrons (above 20 MeV) were only registered at positions near the beam axis (at 0°, 329° and 355°). Neutron spectra, fluence and ambient dose equivalent, H * (10), values of both systems were in good agreement (<15%) while the unfolding code proved to have a limited effect. The highest H * (10) value of 2.7 μ Sv Gy −1 was measured at 329° to the beam axis and 1.63 m from the isocenter where high-energy neutrons ( E ⩾ 20 MeV) contribute with about 53%. The neutron mapping within the gantry room showed that H * (10) values significantly decreased with distance and angular position with respect to the beam axis dropping to 0.52 μ Sv Gy −1 at 90° and 3.35 m. Spectra at angles of 45° and 135° with respect to the beam axis measured here with an anthropomorphic phantom showed a similar peak structure at the thermal, fast and high energy range as in the previous water-tank experiments. Meanwhile, at 90°, small differences at the high-energy range were observed. Using ERBSS systems, neutron spectra mapping was performed to characterize the exposure of scanning proton therapy patients. The ten measured spectra provide precise information about the exposure of healthy organs to thermal, epithermal, evaporation and intra-nuclear cascade neutrons. This comprehensive spectrometry analysis can also help in understanding the tremendous literature data based rem-counters while also being of great value for general neutron shielding and radiation safety studies.